Annual Report on the Working of State Electricity Boards and Electricity Departments, Power and Energy Division Planning Commission Govt. of India April, 1986 - Planning Commission (Planning Commission, 1986)
The Annual Report on the Working of State Electricity Boards (SEBs) and Electricity Departments (EDs) (April 1986) presents a detailed assessment of India’s power sector performance during the Sixth Plan (1980–85) and projections for the early Seventh Plan period (1985–87). Capacity utilization improved modestly, with plant load factors rising from 44.2% to 50%, while transmission and distribution losses remained high, exceeding 21% in many states. Financially, SEBs faced substantial commercial losses of Rs. 1,368 crore in 1985–86, contributing to a cumulative deficit of Rs. 11,757 crore projected for the Seventh Plan. Average energy sale rates rose in most sectors, though agricultural tariffs remained below cost, exacerbating losses. Employment efficiency improved slightly, reflecting a reduction in staff per MW of capacity. The report emphasizes the urgent need for operational reforms, tariff rationalization, enhanced revenue collection, and investment in technology to improve efficiency, reduce losses, and ensure the financial and operational sustainability of SEBs, thereby supporting India’s national energy goals.
Power and Energy Division Planning Commission Govt. of India April 1986
Power and Energy Division Planning Commission Govt. of India April 1986
Keywords: State Electricity Boards; Electricity Departments; Annual Report 1986; Power Sector; Capacity Utilization; Transmission & Distribution Losses; Financial Performance; Commercial Losses; Tariff Structure; Employment Productivity; Operating Ratio; Additional Resource Mobilization; SEB Reforms; Energy Sales; Cost of Supply; Revenue Deficit